Logical Modelling of Statistical Data Using the SDMX Standard: Case Study on the Quarterly Gross Regional Domestic Product Table - Amandasari, Kartika; Pratama, Nano Yulian; Aditama, Farhan Satria; Marsisno, Waris (Politeknik Statistika STIS, 2025)
Poverty, as a national issue, necessitates data-driven policy planning informed byaccurate and consistent statistics. To ensure the optimal quality and consistency of statistical datareporting across diverse regions, the adoption of an international standard is crucial. TheStatistical Data and Metadata Exchange (SDMX) standard facilitates the structured exchange ofdata and metadata. This study aims to design and implement a statistical indicator data modelusing the SDMX standard to improve table consistency. We utilized Quarterly Provincial GrossRegional Domestic Product (GRDP) data as a case study and applied the Design ScienceResearch Method (DSRM) as the methodology. The results demonstrate that modeling theGRDP data using SDMX yields a uniform and highly consistent table structure, significantlyenhancing the consistency of statistical data reporting across regions.